Uncovering the geodetic signature of silent slip through repeating earthquakes. Issue 8 (24th April 2015) - Frank, William B.; Radiguet, Mathilde; Rousset, Baptiste; Shapiro, Nikolaï M.; Husker, Allen L.; Kostoglodov, Vladimir; Cotte, Nathalie; Campillo, Michel
Abstract Slow transient slip that releases stress along the deep roots of plate interfaces is most often observed on regional GPS networks installed at the surface. The detection of slow slip is not trivial if the dislocation along the fault at depth does not generate a geodetic signal greater than the observational noise level. Instead of the typical workflow of comparing independently gathered seismic and geodetic observations to study slow slip, we use repeating low‐frequency earthquakes to reveal a previously unobserved slow slip event. By aligning GPS time series with episodes of low‐frequency earthquake activity and stacking, we identify a repeating transient slip event that generates a displacement at the surface that is hidden under noise prior to stacking. Our results suggest that the geodetic investigation of transient slip guided by seismological information is essential in exploring the spectrum of fault slip.